2019
DOI: 10.9734/jammr/2019/v29i1030131
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus Colonization in Pregnancy: Prevalence, Determinants and Antibacterial Susceptibility Pattern in Sagamu, Nigeria

Abstract: Aims:To establish the prevalence, determinants and the antibiotic susceptibility pattern of Group B streptococcus in pregnant women in Sagamu, Ogun State, Nigeria. Study Design: Prospective cross-sectional study Place and Duration of Study: The study was carried out at the antenatal clinic at Olabisi Onabanjo University Teaching Hospital, Sagamu, Ogun State, Nigeria, between July 2017 and December 2017. Methodology: The study involved 184 pregnant women attending antenatal clinic. Lower vaginal and rectal swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…[ 15 ] who reported the highest prevalence rate between 31 and 35 years and Akadri et al . [ 5 ] whose study recorded the highest prevalence in women above 30 years of age, although there was no significant association between age and GBS colonisation.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…[ 15 ] who reported the highest prevalence rate between 31 and 35 years and Akadri et al . [ 5 ] whose study recorded the highest prevalence in women above 30 years of age, although there was no significant association between age and GBS colonisation.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence recorded in this current study was lower than that reported in China, Ethiopia, South Africa, and in various regions in Nigeria. [ 2 3 4 5 6 13 14 15 ] A wide range of prevalence rates of 8.6–34.2% have been reported in different studies worldwide. [ 2 3 4 5 6 13 14 15 ] These differences including the one observed in our study probably may be due to the different environments and populations in which the various studies were carried out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations